1998
DOI: 10.1007/s12144-998-1020-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trait and situational self-handicapping on competitive anxiety among athletes

Abstract: Initial evidence suggests that the employment of self-handicapping strategies has a beneficial effect on negative affective states associated with the perceived threat of evaluative contexts (Harris & Snyder, 1986;Leary, 1986). The present study sought to describe the type of self-handicapping behaviors demonstrated by youth athletes (N=238) as well as to assess the stress-buffering role of athlete self-handicapping on indices of competitive state anxiety. Specifically, it was hypothesized that among high trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
2
17
1
1
Order By: Relevance
“…The operationalizations of the 4cs have been published in work conducted by Ryska, Yin, and Cooley (1998) as well as Mackenzie (1997).…”
Section: Operationalization Of the 4csmentioning
confidence: 99%
“…The operationalizations of the 4cs have been published in work conducted by Ryska, Yin, and Cooley (1998) as well as Mackenzie (1997).…”
Section: Operationalization Of the 4csmentioning
confidence: 99%
“…10 However, effort has not been directed toward determining whether each has different 11 determinants. The majority of the published sport studies have focused on determinants of 12 claimed self-handicapping (e.g., Kuczka Greenberg, 1983). The few studies that have examined both types have assumed common 15 determinants (e.g., Elliot, Cury, Fryer, & Huguet, 2006; Thompson & Richardson, 2001).…”
mentioning
confidence: 99%
“…Within the self-handicapping 11 literature, feeble self-beliefs have been conceptualised as low self-esteem (see Tice, 1991). 12 Athletes with low self-esteem may not want to risk sabotaging an upcoming performance with a 13 costly behavioral self-handicap, but just in case they do fail, they may desire the protection of a 14 relatively low-risk, claimed self-handicap. Indeed, Martin and Brawley (2002, Study 2) found 15 that low self-esteem was associated with greater claimed self-handicapping prior to a fitness test.…”
mentioning
confidence: 99%
“…Researches showed that anxiety might be used as a self-handicapping strategy (17,18). Various cognitive mechanisms might play a role in development of anxiety and anxiety disorders (19).…”
Section: Introductionmentioning
confidence: 99%